La influencia de la estructura en una empresa en la contabilidad. - Aguilar Cacao, Ariel Argenis (Machala: Universidad Técnica de Machala, 2022)
The organizational structure is understood as the internal systematic arrangement that an entity develops, seeking to ideally manage the planning, direction and management of its processes in order to achieve the objectives set, although for this, a correct implementation is necessary, considering the actions of different areas in the entity such as accounting management. The objective of this investigation is to analyze the influence of the organizational structure on activities related to accounting, identifying the incidence of: teaching and accounting disorganization, deficiency in internal control and financial deterioration, regarding the execution of accounting actions within of the organization. The study was developed under a qualitative approach, based on the historical-logical theoretical method. It was observed that the incidence of the organizational structure affects accounting management, influencing the development of its activities, resulting in: lack of accounting management, insufficient risk analysis and insufficient budgeting.
La estructura organizacional se comprende como la disposición sistemática interna que desarrolla una entidad, buscando gestionar idealmente la planificación, dirección y manejo en sus procesos para lograr obtener los objetivos trazados, aunque para ello, es necesario de una correcta implementación, considerando las acciones de distintas áreas en la entidad como la gestión contable. La presente investigación tiene como objetivo analizar la influencia de la estructura organizacional en actividades relacionadas con la contabilidad, identificando la incidencia de: la desorganización lectiva y contable, la deficiencia en control interno y el deterioro financiero, respecto a la ejecución de las acciones contables dentro de la organización. El estudio se desarrolló bajo un enfoque cualitativo, basado en el método teórico histórico-lógico. Se observó que la incidencia de la estructura organizacional repercute en la gestión contable, influyendo en el desarrollo de sus actividades, derivando en: falta de gestión contable, insuficiente análisis de riesgo e insuficiente elaboración de presupuestos.
Keywords: ESTRUCTURA ORGANIZACIONAL; CONTABILIDAD; GESTIÓN CONTABLE